RET-mediated autophagy suppression as targetable co-dependence in acute myeloid leukemia - Rudat, Saskia Simone; Lutz, Christoph; Fröhling, Stefan; Scholl, Claudia (Leukemia, 2018)
Many cases of AML are associated with mutational activation of receptor tyrosine kinases (RTKs) such as FLT3. However, RTK inhibitors have limited clinical efficacy as single agents, indicating that AML is driven by concomitant activation of different signaling molecules. We used a functional genomic approach to identify RET, encoding an RTK, as an essential gene in multiple subtypes of AML, and observed that AML cells show activation of RET signaling via ARTN/GFRA3 and NRTN/GFRA2 ligand/co-receptor complexes. Interrogation of downstream pathways identified mTORC1-mediated suppression of autophagy and subsequent stabilization of leukemogenic drivers such as mutant FLT3 as important RET effectors. Accordingly, genetic or pharmacologic RET inhibition impaired the growth of FLT3-dependent AML cell lines and was accompanied by upregulation of autophagy and FLT3 depletion. RET dependence was also evident in mouse models of AML and primary AML patient samples, and transcriptome and immunohistochemistry analyses identified elevated RET mRNA levels and co-expression of RET and FLT3 proteins in a substantial proportion of AML patients. Our results indicate that RET-mTORC1 signaling promotes AML through autophagy suppression, suggesting that targeting RET or, more broadly, depletion of leukemogenic drivers via autophagy induction provides a therapeutic opportunity in a relevant subset of AML patients.
Gesehen am 24.04.2019